Mapping of Research Themes on Environmental, Social, and Governance (ESG) Using Leximancer - Permatasari, Ika; Permatasari, Intan Kurnia; Laksono, Bayu Rama; Putikadea, Insyirah; Hidayat, Rendra Arief (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This article presents a study using Leximancer (a text mining tool to visualize themes and concepts in text) to find any themes that still have a great opportunity to be studied further related to ESG. This study used the Scopus database and gathered 159 published articles from 2011 to 2020. The articles were selected based on the analysis of the abstract, the theory used, including the development of hypothesis (if any), and conclusions. Based on the main themes generated by Leximancer software, overall, the ‘social’ theme was the most dominant, while themes such as ‘investor’ and ‘sustainability’ were less dominant. This review reveals that the themes and concepts resulting from Leximancer’s content analysis have not been widely studied in the previous literature. Our study continues the previous literature review with a different scope and method. Leximancer offers a larger list of potentially useful keywords for further analysis and provides a visually appealing display of themes and concepts and their level of importance. The results of this review could be used as a basis for providing academic guidance in future ESG research. Keywords: Leximancer, ESG, ESG themes, ESG concepts.